2001
DOI: 10.1086/322684
|View full text |Cite
|
Sign up to set email alerts
|

Infection withBurkholderia cepaciaComplex Genomovars in Patients with Cystic Fibrosis: Virulent Transmissible Strains of Genomovar III Can ReplaceBurkholderia multivorans

Abstract: Infection with Burkholderia cepacia complex in patients with cystic fibrosis (CF) results in highly variable clinical outcomes. The purpose of this study was to determine if there are genomovar-specific disparities in transmission and disease severity. B. cepacia complex was recovered from 62 patients with CF on > or =1 occasions (genomovar III, 46 patients; genomovar II [B. multivorans], 19 patients; genomovar IV [B. stabilis], 1 patient; genomovar V [B. vietnamiensis], 1 patient; and an unclassified B. cepac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
195
1
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(206 citation statements)
references
References 31 publications
7
195
1
3
Order By: Relevance
“…In this study, we performed random amplified polymorphic DNA (RAPD) analysis (Mahenthiralingam et al, 1996) and macrorestriction typing followed by PFGE (Mahenthiralingam et al, 2001) to investigate genetic relatedness between Czech clinical isolates and to compare them with major epidemic strains from other CF centres. In addition, the isolates were also screened for the presence of genetic markers of strain transmissibility, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we performed random amplified polymorphic DNA (RAPD) analysis (Mahenthiralingam et al, 1996) and macrorestriction typing followed by PFGE (Mahenthiralingam et al, 2001) to investigate genetic relatedness between Czech clinical isolates and to compare them with major epidemic strains from other CF centres. In addition, the isolates were also screened for the presence of genetic markers of strain transmissibility, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are important since they show that genomovar IIIa strains would be able to generate the m-oxo oligomer from any free iron(III) protoporphyrin IX monomers both in the healthy lung (at neutral pH) and under the slightly lower pH conditions which may prevail during chronic lung inflammation. These observations may explain why epidemic genomovar IIIa strains are frequently found able to superinfect lungs already colonized by other species, including Pseudomonas aeruginosa and other B. cepacia genomovars (Hart & Winstanley, 2002;Mahenthiralingam et al, 2001) where, in the presence of chronic inflammation, the pH is likely to be lower than neutral (Bodem et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…A survey of a previously well-characterized panel of strains belonging to the Burkholderia cepacia complex (Mahenthiralingam et al, 2000(Mahenthiralingam et al, , 2001 has revealed the possession of a putative 97 kDa haem-binding protein (HBP) by epidemic strains of genomovar IIIa (Smalley et al, 2001). Such isolates have been described as highly transmissible among cystic fibrosis (CF) patients (Mahenthiralingam et al, 2001) and can cause the socalled 'cepacia syndrome', a necrotizing pneumonia leading to a fatal clinical deterioration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ET12 epidemic lineage encodes a cable pilus that can assist in binding to both mucins [84] and host tissue [85], and isolates have been shown to dominate and replace infections originally caused by B. multivorans [86].…”
Section: Burkholderia Cenocepaciamentioning
confidence: 99%